Sho 'em all - Busiek, Kurt 1960- (Homage Comics, 1997)
Presents stories about the heroes, villains, and other citizens who inhabit the cartoon world of Astro City, and the crimes and mysteries that accompany them
Keywords: Science fiction comic books, strips, etc; Graphic novels